The THE EFFECTIVENESS OF RATIONALITY AND SPIRITUALITY INTEGRATION IN ITB SPIRITUAL COCUURICULAR CAMP TO INCREASE RELIGIOUS SPIRIT AND CREATE STUDENTS WITH NON-RADICAL MILITANT WISDOM: Penelitian di Institut Teknologi Bandung - Asep Zaenal Ausop (Fakultas Seni Rupa dan Desain ITB, 2021)
Many people misunderstand that the ITB Spiritual Camp (ITB SC) is considered a duplication of co-curricular activitiesof Islamic education. This research proves that ITB SC activities are different from intra-curricular activities. ITB-SChas sharpened and enhanced the point of moral spirituality, while the intra-curricular activities have enhanced andsharpened students’ rationality of science, philosophy, and the application of technology. The research uses mixedmethod. Analysis of the problems was conducted using theological, philosophical, and scientific approaches. Sourcesof data were taken from mosque leaders of Salman ITB, senior lecturers, mentors, and students participating in ITB SC.Research instrument comprised interviews, participant observations, and questionnaires. This research is based on thecorridor of Socio-technology. In conclusion, ITB-SC has a potential to harmoniously integrate rationality of science andtechnology as well as moral spirituality. ITB-SC has the potential to support changes in the culture of the implementationof Islamic Religious Education, which was previously centered on intra-curricular activities, shifting some of it to the cocurricular paths such as what happened in the ITB Spiritual Camp.